2021
DOI: 10.1007/s00125-021-05578-1
|View full text |Cite
|
Sign up to set email alerts
|

Flash monitor initiation is associated with improvements in HbA1c levels and DKA rates among people with type 1 diabetes in Scotland: a retrospective nationwide observational study

Abstract: Aims/hypothesis We assessed the real-world effect of flash monitor (FM) usage on HbA1c levels and diabetic ketoacidosis (DKA) and severe hospitalised hypoglycaemia (SHH) rates among people with type 1 diabetes in Scotland and across sociodemographic strata within this population. Methods This study was retrospective, observational and registry based. Using the national diabetes registry, 14,682 individuals using an FM at any point between 2014 and mid-2020… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 32 publications
(63 reference statements)
3
11
0
Order By: Relevance
“…With two recent analyses, we were able to reassure policymakers in the National Health Service in Scotland that investment in free provision of continuous subcutaneous insulin infusion (CSII) pumps and flash monitors is having an impact on important outcomes. We showed10 that flash monitor initiation was associated with clinically important reductions in HbA1c, especially in those with worst glycaemic control; an average fall of 15.5 mmol/mol (1.4% units) in those with HbA1c>84 mmol/mol (9.8%) for example. We also showed a striking 40% reduction in diabetic ketoacidosis incidence with flash monitor use.…”
Section: Findings To Datementioning
confidence: 85%
“…With two recent analyses, we were able to reassure policymakers in the National Health Service in Scotland that investment in free provision of continuous subcutaneous insulin infusion (CSII) pumps and flash monitors is having an impact on important outcomes. We showed10 that flash monitor initiation was associated with clinically important reductions in HbA1c, especially in those with worst glycaemic control; an average fall of 15.5 mmol/mol (1.4% units) in those with HbA1c>84 mmol/mol (9.8%) for example. We also showed a striking 40% reduction in diabetic ketoacidosis incidence with flash monitor use.…”
Section: Findings To Datementioning
confidence: 85%
“…The magnitude of the improvement that we show is larger than the HbA 1c drop of 0.2% associated with flash monitor initiation, reported by a nationwide Scottish observational study. 27 …”
Section: Discussionmentioning
confidence: 99%
“…Several studies 18,19,23,25 have shown the significant benefit of isCGM on resource utilisation in people living with diabetes. For example, Jeyam et al 23 analysed data from the Scottish diabetes registry and showed a 41% reduction in DKA using isCGM in the Scottish diabetes registry. In the present study, we show similar estimates with 43% reductions in hospital admissions due to hyperglycaemia/ DKA.…”
Section: Discussionmentioning
confidence: 99%